2017
DOI: 10.1158/0008-5472.can-17-0150
|View full text |Cite
|
Sign up to set email alerts
|

PADI2-Mediated Citrullination Promotes Prostate Cancer Progression

Abstract: Onset of castration-resistance prostate cancer (CRPC) after long-term androgen deprivation therapy remains a major obstacle in the treatment of prostate cancer. The peptidylarginine deiminase PADI2 has been implicated in chronic inflammatory diseases and cancer. Here we show that is an androgen-repressed gene and is upregulated in CRPC. PADI2 expression was required for survival and cell-cycle progression of prostate cancer cells, and PADI2 promoted proliferation of prostate cancer cells under androgen-deprive… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
87
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(87 citation statements)
references
References 50 publications
0
87
0
Order By: Relevance
“…Although tumor-associated PAD2 was overexpressed in biopsies from patients with castration-resistant prostate cancer (CRPC; ref. 40), a downregulation of intertumoral PAD2 expression was identified in a cohort of patient with colorectal cancer specimens in comparison with normal mucosa of healthy control tissues (41).…”
Section: Prevalence Of Pads In Tumor Tissuesmentioning
confidence: 99%
See 2 more Smart Citations
“…Although tumor-associated PAD2 was overexpressed in biopsies from patients with castration-resistant prostate cancer (CRPC; ref. 40), a downregulation of intertumoral PAD2 expression was identified in a cohort of patient with colorectal cancer specimens in comparison with normal mucosa of healthy control tissues (41).…”
Section: Prevalence Of Pads In Tumor Tissuesmentioning
confidence: 99%
“…In particular, PAD2-driven citrullination in the nucleus activated the androgen receptor pathway, whereas PAD2 stabilized the androgen receptor and promoted its translocation to the nucleus. Prostate cancer cells treated with PAD inhibitor Cl-amidine and PAD2-knockdown prostate cancer cells both exhibited a delay in cancer progression in vitro and in vivo (40). The authors, however, did not explore which proteins and residues were citrullinated, thus providing little mechanistic explanation for the observed findings.…”
Section: Citrullination Affecting Cancer Cell Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…The host has also intrinsic sources of citrullination through genes coding for a family of five calcium-dependent enzymes named peptidyl-arginine deiminases (PAD 1, 2, 3, 4/5 and 6), which are quite similar but not identical to PPAD. The host PADs have been linked to various human and animal cancers [94][95][96][97]. Thus, Kholia et al [96] reported that the expression level of PAD2 and PAD4 and the deimination of cytoskeletal actin were increased during stimulation of prostate cancer cells (PC3) with microvesiculate, which is involved in the progression of cancer.…”
Section: Potential Role Of Peptidyl Arginine Deiminases and Protein Cmentioning
confidence: 99%
“…Peptidylarginine-deiminase (PADI2), known to catalyze the posttranslational deamination of proteins, is associated with increased AR levels in CRPC by protecting it from UPD. 40 BMI1, a Polycomb group protein (PcG), stabilizes both AR and AR-V7 splice variant by physical interaction at the N-terminus of AR and thereby masking the MDM2 binding site required for degradation by proteasome. 41 This observation raises the possibility of other factors being necessary for AR chromatin occupancy, to modulate AR stability.…”
Section: Proteasomal-and Nonproteasomal-mediated Degradation Of Armentioning
confidence: 99%